PENENTUAN HARGA JUAL PESANAN KHUSUS DAUN PINTU PANEL BENGKIRAI PADA CV ARINDA DI SAMARINDA - ., Asmah (EKONOMIA, 2013)
One of the company engaged in processing raw wood into the door leaf is CV. Arinda located at Jalan P.M. Noor RT No. 12. 27 Samarinda. The company manufactures doors and windows.Doors are ordered by one of the developer in the city of Samarinda in March is the standard bengkirai door (size: 82cm x 210cm) as many as 122 units at the normal price of Rp. 800.000, - per unit, then do a special order 22 units by asking for a price cut of 15% of the normal price. Reason asking price cuts because the number of orders pretty much, the problem is Is the selling price of a special order bengkirai panel doors with a standard 15% discount, still provide benefits. Knowing the purpose of this study calculating the selling price bengkirai order leaves the door panel on a standard CV. Arinda and obtain information regarding the reasonable costs to be taken into account in determining the selling price of a special order. Basic theories used in management accounting, the tool is used analysis Variable Costing BasedThe results of the analysis and discussion:CV Arinda producing Bengkirai panel doors with regular orders that the cost of production using the method of full costing as much as 122 sheets of benefit CV Arinda to accept special orders by 22 Bengkirai panel doors that calculation of the cost of production using Variable Costing method to get additional benefits Accept special orders CV Arinda benefit, thus the hypothesis that allegedly selling price special orders with a 15% discount still provide benefits, acceptable.